The constitution of naüne (body) among the yunatügü (tikuna) (2014)
The yunatügü (Tikuna) perceive the na (beings) as possessing four fundamental principles: pora (power), naẽ (thought), maü̃ (vitality) y kua̰ (knowledge). For the yuukü (healer) the human body is a web of tü (strings) of tobacco smoke. The bodies are interconnected with Naaane (territory, cosmos) by means of these tü, planted in the body; through them, the positive and negative energies enter and leave the body, and through them we can be victims of the evil yuukü and of the ngo̰ogü (spirits). The body is a flux of energy that is in constant readjustment, intimately linked to the sociocultural organization of the group. The Tikuna must carry out constant actions and respect prohibitions in order to attain these adjustments, which constitute personal and collective relationships with animals, plants, natural phenomena and visible and invisible beings. It is here that the action of the yuukü works as a means for the social and individual bodily balance.